The effectiveness of the virtual reading gym online intervention for grade three to six learners with reading difficulties - Dean, Jessica (Division of Communication Sciences and Disorders, 2020)
Background: Research suggests that most South African learners are not achieving the expected literacy outcomes of their grades. Compounding the literacy crisis is the paucity of South African research related to information and communication technology (ICT)-based reading intervention, which may have potential for population-based service delivery. Aims and Objectives The aim of the study was to determine the effectiveness of the Virtual Reading Gym (VRG) online intervention for grade 3 to 6 learners with reading difficulties. The objective was to describe changes in learners’ reading skills (accuracy, rate, vocabulary and comprehension) after VRG intervention. Design Two studies were carried out: (1) A retrospective analysis used data from a previous study conducted in mainstream schools which used peer reading mentors; (2) A prospective study in a school for learners with special educational needs that had speech-language therapist led intervention. Both studies used matched subject pre/ post intervention designs. Methods and Procedures In Study 1, matched pairs were retrospectively created to form a sample (n=20, 8 males and 12 females, 10 intervention group and 10 control group) of grade 3 to 6 learners. In Study 2, the prospective study, participants (n=20, 14 males and 6 females, 10 intervention group and 10 control group) were grade 3 to 6 learners from a school for learners with special educational needs in Cape Town. For both studies, the intervention group received VRG intervention 3 times per week (30 minutes per session) for 10 weeks. The control group continued with regular school activities. Independent samples t-tests for gain scores were used to analyse results. Semi-structured interviews were conducted with intervention participants from the prospective study. Thematic analysis was used to interpret the transcribed interview data. 5 Results For the retrospective analysis there were no statistically significant differences between the intervention and control groups’ reading accuracy, rate, vocabulary and comprehension improvements at the completion of the VRG intervention. Similarly, the prospective study found no statistically significant differences between the reading accuracy, vocabulary or comprehension gains of learners in the intervention and control groups. However, there was a statistically significant difference between the groups’ gains on one measure of reading rate. The thematic analysis findings were that learners expressed enjoyment of the VRG and intervention experiences, valued the role of the reading partners, believed they had made literacy skill gains, described self-competency improvements, expressed the belief that the VRG could result in reading improvements, and portrayed positive attitudinal and behavioural changes related to reading. Discussion The study contributes by investigating the potential of one practical solution to South African learners’ reading difficulties and adding to the limited local evidence base on ICT reading intervention. Although an intervention effect could not be demonstrated in this study, the changes noted in reading rate and qualitative findings suggest the potential for impact. The discussion considers some explanations for the findings, suggestions for improving interventions such as the VRG, and lines of future research that could be developed to support South African children in their struggles with reading.